1982
DOI: 10.1111/j.1440-169x.1982.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and Cytochemistry of the Cell Types in the Larval Hematopoietic Organs and Hemolymph of Drosophila Melanogaster. (drosophila/hematopoiesis/blool cells/ultrastructure/cytochemistry)

Abstract: The ultrastructure of the primordial blood cells in the first and second hematopoietic lobes of the late second and third instar larva and prepupa of Drosophila melunogaster was compared with the ultrastructure of the blood cells found freely in the larval hemolymph. Within the hematopoietic lobes two principal cell-types were detected : (i) the prohemocytes and proplasmatocytes, and (ii) different developmental stages of crystal cells., Prohemocytes are characterized by a ribsome-rich cytoplasm, showing small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 46 publications
3
97
0
Order By: Relevance
“…The main differences between pseudopodocytes and plasmatocytes are their size and the numerous pseudopodia present at the surface of the pseudopodocytes. Another hemocyte type called podocyte was previously described in D. melanogaster showing similar cytoplasmic extensions (Rizki and Rizki, 1980;Shrestha and Gateff, 1982). These cells also showed the same ultrastructural characteristics as the ones of plasmatocytes, and were then considered as a possible intermediate stage of plasmatocytes differentiating into lamellocytes.…”
Section: Discussionmentioning
confidence: 72%
“…The main differences between pseudopodocytes and plasmatocytes are their size and the numerous pseudopodia present at the surface of the pseudopodocytes. Another hemocyte type called podocyte was previously described in D. melanogaster showing similar cytoplasmic extensions (Rizki and Rizki, 1980;Shrestha and Gateff, 1982). These cells also showed the same ultrastructural characteristics as the ones of plasmatocytes, and were then considered as a possible intermediate stage of plasmatocytes differentiating into lamellocytes.…”
Section: Discussionmentioning
confidence: 72%
“…The haemolymph does not play a role in oxygen transport but is the major site of resistance during systemic infection. Drosophila larvae and adults contain a few thousand blood cells, which can be divided into the following four types on the basis of structural and functional features: secretory cells; plasmatocytes (the most numerous cells, essentially phagocytic); lamellocytes (required for encapsulation of parasites); and crystal cells (involved in the melanization process) [4,5,6 •• ]. Drosophila haematopoiesis occurs in two major phases.…”
Section: Haemocyte Differentiation and Functionmentioning
confidence: 99%
“…Many molecular and cellular aspects of hemocyte development and responses are well conserved between Drosophila and vertebrates Hartenstein, 2006;Lemaitre and Hoffmann, 2007;Martinez-Agosto et al, 2007). In Drosophila, undifferentiated prohemocyte progenitors and three differentiated blood cell lineages are being distinguished (Rizki, 1978;Shrestha and Gateff, 1982;Lanot et al, 2001;Hartenstein, 2006). Macrophages, or plasmatocytes, that express Peroxidasin (Pxn) (Nelson et al, 1994;Tepass et al, 1994;Stramer et al, 2005) and Hemolectin (Hml) (Goto et al, 2001;Sinenko and Mathey-Prevot, 2004), correspond to vertebrate myeloid cells and represent 90-95% of hemocytes at most developmental stages (Tepass et al, 1994;Lanot et al, 2001;.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports described a population of posterior dorsal-vessel-associated sessile hemocytes as a hematopoietic compartment that is actively involved in larval immunity (Shrestha and Gateff, 1982;Stofanko et al, 2008;Markus et al, 2009), and cell transplantation experiments suggested persistence of embryonic hemocytes (Holz et al, 2003). Because these reports left important open questions regarding the lineage, anatomical locations and inductive microenvironments, we systematically investigated the biology of the Drosophila larval hematopoietic system.…”
Section: Introductionmentioning
confidence: 99%